Entre a academia o mercado - onde comunicação e marketing se encontram : um estudo de caso da Rede Petrográs SE - Carlos, Aneliese de Castro (2017)
This paper proposes a discussion about the link between organizational communication and marketing. Although they are related subjects, they are often analyzed under different perspectives. Its general objective is to understand how the integration between communication and marketing occurs, both in theory and in practice, observing as an example cases companies participating in the Petrogás SE Network. These companies are certified by ISO and audited periodically, in addition it has as system of management the Integrated Management System (SGI). From the protocol created by Yin (2015) a research was done on how the integrated communication of marketing has been worked in these institutional environments. Our intention was to understand if having an Integrated Management System makes the communication and marketing of these companies professional or close to what is said in theory. In order to do so, a qualitative research was done using the methodology. Unique and holistic case study proposed by Yin (2015), being used as participant observation method and semi-structured interviews. Through the study it can be seen that even in the strict methods proposed by international norms, both communication and marketing have been neglected in these institutions. There is a great lack of knowledge and lack of preparation regarding the areas addressed by the administrators and the absence of specific professionals to implement organizational communication actions and their integration into marketing.